The mechanism of glucocorticoid receptor dependent regulation of NRF2 activity - 권지영 (The Graduate School, Ajou University, 2022)
Nuclear factor E2-related factor 2 (NRF2) plays a key role in redox metabolism and antioxidant defense. Recent studies showed that abnormal activation of NRF2 is a common event in many types of cancer suggesting that NRF2 could be a promosing target for cancer therapy. Previously, we identified clobetasol propionate (CP), a glucocorticoid analogue as the most potent NRF2 inhibitor from a clinical compound library screening. In addition, we also reported that CP inhibits NRF2 through glucocorticoid receptor (GCR) and β-TrCP -dependent proteasomal degradation of NRF2. In the present study, we further investigated the mechanisms of CP on NRF2 inhibition and the crosstalk between GR and NRF2. Either inhibition of protein synthesis by cycloheximide (CHX) or CP rapidly induced degradation of NRF2 protein in 1hr or 2hr, respectively. In addition, NRF2 degradation was further accelerated in the presence of both CHX and CP, supporting the finding that CP promotes NRF2 protein degradation. Using the DNA non-binding mutants of GCR, we also confirmed that the effect of CP on NRF2 inhibition is independent on the transcriptional activity, rather dependent on non-genomic activity of GCR. Interestingly, the non-genomic mechanism is also supported by the finding that XA compound, which we identified from the screening, suppressed CP-induced GCR transcriptional activity without compromising CP-induced NRF2 inhibition. Indeed, we confirmed that GCR co-immunoprecipitaed with NRF2. Finally, we also found regulatory crosstalk between GCR and NRF2, which GCR can promote the expression and activity of NRF2 while NRF2 can suppress GCR expression and activity. Taken together, our data demonstrate the novel mechanisms of GCR-dependent NRF2 inhibition and their cross-regulatory network.
학위논문(석사)--아주대학교 일반대학원 :약학과,2022. 2
Keywords: NRF2; glucocorticoid